(untitled) (Revista Brasileira Multidisciplinar, 2024)
Resolution nº 41 of the Tripartite Intermanagement Commission, of October 31, 2018, inserts Palliative Care into continuous care integrated at any point in the Health Care Network, offered by multidisciplinary teams, which includes Professional of Physical Educatio (PPE). However, gaps are observed in the literature on the role of PEF in Palliative Care (PC), which stimulates the debate about expanding the horizon of action of PPE, in terms of knowledge, skills and attitudes needed in PC. The practice in the context of PC is important in terms of care during the course of illness, end-of-life care, and mourning. Thus, we present ways for PPE to act in this multiprofessional field of action as part of a complete health care. Thus, it is proposed to qualify the performance of PPE and improve the quality of care provided to patients and their families in PC.